2008
DOI: 10.1161/hypertensionaha.108.117358
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Preeclampsia

Abstract: Abstract-Because early and late preeclampsia (PE) are thought to be different disease entities, we compared maternal cardiac function at 24 weeks gestation in a group of normotensive asymptomatic patients with subsequent development of early (Ͻ34 weeks gestation) and late (Ն34 weeks gestation) PE (blood pressure Ͼ140/90ϩproteinuria Ͼ300 mg/dL) to detect possible early differences in the hemodynamic state. ; PϽ0.001). Early and late PE appear to develop from different hemodynamic states. Late PE appears to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
224
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(261 citation statements)
references
References 33 publications
9
224
0
9
Order By: Relevance
“…Women at the highest risk of developing a hypertensive disorder of pregnancy exhibit a distinct cardiovascular, placental and clinical phenotype before the development of hypertension, consistent with previous reports 3, 9, 16, 17. To the best of our knowledge, this is the first analysis to evaluate clinical characteristics in a consolidated manner, rather than individually.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women at the highest risk of developing a hypertensive disorder of pregnancy exhibit a distinct cardiovascular, placental and clinical phenotype before the development of hypertension, consistent with previous reports 3, 9, 16, 17. To the best of our knowledge, this is the first analysis to evaluate clinical characteristics in a consolidated manner, rather than individually.…”
Section: Discussionsupporting
confidence: 89%
“…It is well accepted that the majority of pregnant women who subsequently develop hypertension in pregnancy exhibit abnormalities in maternal hemodynamics before the clinical development of hypertension, with or without aberrations in circulating angiogenic proteins that regulate vascular function early in pregnancy 3, 4, 5. The clinical syndromes of hypertension in pregnancy are distinctly heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Although some echocardiographic studies showed that women developing hypertensive complications during pregnancy may have different LA dimensions than controls, [23][24][25][26] the potential link between LA abnormality detected early in pregnancy by echocardiography or ECG and development of hypertensive disorders remains elusive. However, some possible mechanisms are supported by epidemiological data and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset preeclampsia is strongly associated with placental disease characterized by maternal vascular malperfusion, where the abnormal placental villi secrete excessive amounts of antiangiogenic proteins and reduced levels of pro-angiogenic proteins into the maternal circulation [7][8][9]. Women with early-onset disease, typically associated with FGR, develop hypertension earlier in pregnancy that is characterized by increased systemic vascular resistance, reduced cardiac output and stroke volume along with relative bradycardia [5]. In contrast, late-onset preeclampsia is less commonly associated with severe placental disease, and consequently exhibits less dramatic alterations in the circulating levels of placentalderived angiogenic proteins [8,10].…”
Section: Preeclampsia Preventionmentioning
confidence: 99%
“…Only 1% of pregnant women develop early-onset preeclampsia, where both the maternal and fetal implications are substantially greater, typically resulting in FGR and the need for iatrogenic preterm delivery before 34 weeks' gestation [2]. Early-onset preeclampsia is hypothesized to be a direct consequence of the interactions between a dysfunctional placenta and maternal cardiovascular system, while late-onset preeclampsia is hypothesized to be largely triggered by maternal constitutional factors [3][4][5]. Typically, women with early-onset preeclampsia present with an acute, severe syndrome that threatens the life of both the mother and her fetus.…”
mentioning
confidence: 99%